Representasi Budaya Jawa dalam Film “Lagi-Lagi Ateng” Karya Monty Tiwa serta Implementasinya sebagai Bahan Ajar BIPA Tingkat Mahir - Tiya Agustina (Jurnal Bahasa Indonesia bagi Penutur Asing, 2021)
AbstractThere are many ways to improve the quality of BIPA institutions, one of which is through teaching materials. Films can be used as an alternative choice of media for delivering teaching materials in introducing language and culture to foreign students. This research is a qualitative descriptive study with a content analysis strategy in the film "Lagi-Lagi Ateng" by Monty Tiwa. The data sources in this research are shot/sequence/scene and dialogue text contained in the film. The data collection technique used the listening and note-taking technique. The data validity technique uses source triangulation and theory. Finally, the data analysis technique uses the Miles & Huberman model. Based on the results and discussion, it was found that the cultural aspects of objects in the film "Lagi-Lagi Ateng" include, among others, a) clothing, in the form of palace clothing and buns, b) technology, in the form of wooden rakes and buffalo for plowing the fields, c) cultural arts, in the form of caping and songong, and d) typical food such as tempeh. The representation of Javanese culture in the category of non-object culture includes, among others, a) belief, in the form of kejawen which has animist and shamanic belief patterns, b) values and norms, in the form of adjusting attitudes and speech aimed at creating harmony between human beings. This teaching material can be developed based on the innovativeness of the teacher.Keywords: Cultural Representation, Film, BIPA